Auditoría de gestión al gobierno autónomo descentralizado parroquial rural la canela, cantón Palanda, periodo 2020. - Zurita Bustamante, Kerly Manuela (2022)
The Curriculum Integration Work entitled: MANAGEMENT AUDIT OF THE DECENTRALIZED RURAL PARISH AUTONOMOUS GOVERNMENT LA CANELA, PALANDA CANTON, PERIOD 2020, was developed with the purpose of evaluating the internal control system and verifying the level of compliance with the applicable legal and regulatory provisions to the operations carried out by the GAD; and through the application of management indicators, measure the degree of efficiency, effectiveness and economy with which it carries out its activities, in order to issue conclusions and recommendations that allow improving the entity's management. In order to fulfill the objectives of this work, research methods and the management audit process were used that facilitated the collection of information, it began with the preparation of the work order, initial notification, brand sheet, indices, distribution of time and work; Among the main results obtained, it was evidenced; the lack of a Code of Ethics, strategic planning, the lack of application of management indicators, training programs, evaluation of the entity's personnel and control of attendance and punctuality for GAD servers; as it was also verified that of the projects and programs proposed for 2020, 75% were executed, pending the construction of the vehicular bridge over the La Jibara ravine and maintenance of the horseshoe roads of the La Canela Parish. Once the investigative work is completed, it is concluded that the evaluation of the Autonomous Decentralized Rural Parish Government of La Canela is very important, through a management audit, which facilitates its authorities to undertake a change for the readjustment of its management in benefit of the Entity and the inhabitants of La Canela.